Effects of alternative and successive resistance training methods on the muscle fatigue of concentric and eccentric contractions in healthy male individuals - Kadota, Masafumi; Nakamura, Masatoshi; Yoshida, Riku; Takeuchi, Kosuke (Frontiers in Sports and Active Living, 2025)
IntroductionThe effects of alternative and successive training on muscle fatigue profiles of concentric (CON) and eccentric (ECC) contractions were examined.MethodsSeventeen untrained men performed alternative and successive training with maximum isokinetic muscle contractions. In alternative training, three sets of knee flexion and extension exercises were alternatively performed with a 60-s rest interval. Successive training completed three sets of knee flexion exercises followed by three sets of knee extension exercises with a 60-s rest interval. Muscle strength and training volume were measured.Results and DiscussionsKnee flexion muscle strength did not change in either the CON (p = 0.148) or ECC phases (p = 0.073). Knee extension muscle strength decreased in the CON phase (p = 0.004), but it did not change in the ECC phase (p = 0.415). The training volume of knee flexion decreased with each set in the CON phase (p < 0.01), but it decreased in Set 3 in the ECC phase (p < 0.01). The training volume of knee extension decreased with each set in the CON phase (p < 0.01), but it showed no change between sets in the ECC phase (p > 0.05). Alternative training had a lower rate of the change of decrease in training volume for knee extension than did successive training (p < 0.05). The total training volume was higher in alternative training than in successive training (p < 0.05). These results indicated that the ECC phase had less fatiguability than the CON phase, regardless of training methods. Moreover, the alternative training used in this study resulted in less muscle fatigue in the quadriceps and a larger total training volume than the successive training.